2019
DOI: 10.1111/apa.15036
|View full text |Cite
|
Sign up to set email alerts
|

Distinct age‐related patterns of overweight development to guide school healthcare interventions

Abstract: Aim We aimed to identify groups of primary school children with similar overweight development, reveal age‐related patterns of overweight development in the resulting groups and analyse overweight‐related school healthcare interventions. Methods This retrospective longitudinal register study utilised electronic health records from six primary school years. From a random sample of 2000 sixth graders, we derived a study cohort of 508 children meeting criteria for overweight at least once during primary school. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Longitudinal data from children born 1997–1999 in Sweden show that children with overweight or obesity at five years of age tend to remain living with overweight or obesity later in childhood 5 . However, there is also considerable new development of obesity 2,4,6 . Early interventions targeting children with obesity 5–13 years of age serve as attractive opportunities for promoting a healthy lifestyle aiming at reducing future risk of obesity and associated health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal data from children born 1997–1999 in Sweden show that children with overweight or obesity at five years of age tend to remain living with overweight or obesity later in childhood 5 . However, there is also considerable new development of obesity 2,4,6 . Early interventions targeting children with obesity 5–13 years of age serve as attractive opportunities for promoting a healthy lifestyle aiming at reducing future risk of obesity and associated health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses wished that the school doctor would address their concerns regarding over half of the children in grades one and five, which is surprisingly high. Children in other grades rarely meet a school doctor even when they have special health care needs, for example, related to overweight or obesity [ 27 ]. However, many health problems would be most efficiently detected and managed in the school [ 28 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally the factors affecting the development of BMI have been studied cross‐sectionally 2,3,7,13 . However, examining BMI trajectories is an opportunity to understand better longitudinal growth patterns and related factors 9,14–17 …”
Section: Introductionmentioning
confidence: 99%
“…2,3,7,13 However, examining BMI trajectories is an opportunity to understand better longitudinal growth patterns and related factors. 9,[14][15][16][17] Our previous longitudinal growth study identified two BMI trajectories that predicted the development of overweight in early childhood. These were a stable high or low BMI at birth and excessive weight gain after the adiposity rebound.…”
Section: Introductionmentioning
confidence: 99%